2009
DOI: 10.2119/molmed.2009.00140
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of MGMT and RARβ Promoter Methylation in Primary Glioblastomas: Association with Histopathological Characteristics, Inflammatory Mediators and Clinical Outcome

Abstract: Glioblastomas, the most frequent primary brain tumors in adults, are characterized by a highly aggressive, inflammatory and angiogenic phenotype. Methylation of CpG islands in cancer-related genes may serve as an epigenetic biomarker for glioblastoma diagnosis and prognosis. The aim of this study was to analyze the methylation status of four critical tumor-associated genes (MGMT, RARβ, RASSF1A, CDH13), and investigate possible links with inflammatory (interleukin [IL]-6, IL-8) and angiogenic mediators (vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Our results are also in keeping with most studies showing MGMT epigenetic silencing in higher grade and more aggressive tumors arising outside the pituitary gland [22,23]. Piperi et al reported MGMT promoter methylation in 59% of the 17 GBMs studied, and that a correlation existed between methylation status and patient survival, thus suggesting methylation is a prognostic indicator [22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are also in keeping with most studies showing MGMT epigenetic silencing in higher grade and more aggressive tumors arising outside the pituitary gland [22,23]. Piperi et al reported MGMT promoter methylation in 59% of the 17 GBMs studied, and that a correlation existed between methylation status and patient survival, thus suggesting methylation is a prognostic indicator [22].…”
Section: Discussionsupporting
confidence: 92%
“…Epigenetic silencing of MGMT via methylation of its promoter is associated with higher tumor grade and with prognosis in several human neoplasms [3,[22][23][24][25][26][27][28][29]. Accordingly, we report MGMT promoter methylation in 33% of pituitary carcinomas and in 42% of SS3 adenomas.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This regulatory system of gene expression is under the control of cytokines network. In 2010, Piperi et al demonstrated the correlation between IL-6 and the promoter methylation profile of 3 genes RARb, MGMT (mainly in astrocytoma, anaplastic astrocytoma, and secondary glioblastoma) and RASSF1A [94]. O6-methylguanine-DNA methyltransferase (MGMT) is a DNA repair enzyme and its down regulation in normal cells is crucial for carcinogenesis [95].…”
Section: Cytokine Regulation In Gliomasmentioning
confidence: 99%